Alterations in comprehensive geriatric assessment decrease survival of elderly patients with cancer. (February 2018) - Frasca, M.; Soubeyran, P.; Bellera, C.; Rainfray, M.; Leffondre, K.; Mathoulin-Pélissier, S.; ,
Abstract: Introduction: A comprehensive geriatric assessment (CGA) evaluating several domains of health is recommended for elderly patients with cancer. Effects of altered domains on the risk of death in this population need to be clarified. The aim of this study was to estimate the independent association of each CGA domain to overall survival (OS). Method: Patients included in the ONCODAGE cohort completed a CGA at baseline. Cox models (one per domain) estimated the hazard ratio (HR) of death for each CGA domain. Directed Acyclic Graphs (DAGs) selected specific sets of adjustment factors for each model. Results: The analysis included 1264 patients (mean age: 78 years, women: 70%). Median follow-up was 5.2 years, and 446 patients died. Each altered domain had a detrimental effect on survival, sometimes dependent on gender, age, education or time from inclusion. Nutritional status had a time-varying effect, with higher mortality rates if altered only within the first 3 years of follow-up. In case of altered mobility, the risk of death was higher only for the youngest patients and, in case of altered autonomy, only for the youngest women. An altered neurological state led to higher mortality rates; this effect increased with the level of education. Patients with altered psychological status or more than four comorbidities at baseline had also higher mortality rates. Conclusions: Patients with an altered CGA domain have a higher risk of death than those without any alteration. The effect of some alterations is different in some subgroups or at a given time of the treatments. Highlights: The effect of each comprehensive geriatric assessment (CGA) domain on survival was independently estimated and adjusted. All CGA domains, when altered, increased mortality in this population of elderly patients with cancer. The effect of some CGA domains on survival varied according to gender, age, education level or time of follow-up. Effects of autonomy, mobility, cognition or nutrition should be interpreted based on patients' characteristics.